Pemanfaatan Citra Satelit Untuk Menganalisis Kualitas Lingkungan Permukiman di Kecamatan Pekalongan Selatan Kota Pekalongan - Gayuh, Supangkat; Erni, Suharini; Budi, Sanjoto Tjaturahono (Geo-Image, 2018)
Increased population growth always bring a change of one is the change in the level of environmental quality neighborhoods. The availability of space in the city's fixed and finite, then the alternative elections occurred naturally in the space to meet the need for housing and the building of settlements performed ignoring about environmental quality neighborhoods. These parameters include the density of building settlements, settlement building layout, the width of the entrance of the settlement, the settlement's entrance road conditions, location of settlements, and a protective tree driveway neighborhoods. To help the analysis process by making use of remote sensing technology for the mapping, and using software SIG. The method is using score (scoring), stack bundles (overlay). The result of the overlay map quality neighborhoods in district of Pekalongan Selatan, Pekalongan. From this research it can be known that settlements in Pekalongan South with good quality with an area of 60.9 Hectares, better quality with extensive 373.9 Ha, bad quality and with an area of 89.1 Ha. The results of the settlement in the South dominated by the Pekalongan neighborhoods with better quality.